An Energy-interference-free Hardware/Software Debugger for Intermittent Energy-harvesting Systems - Colin, Alexei; Harvey, Graham; Sample, Alanson; Lucia, Brandon (IEEE MICRO, 2017)
Energy-autonomous computing devices have the potential to extend the reach of computing to a scale beyond eitherwired or battery-powered systems. However, these devices pose a unique set of challenges to application developerswho lack both hardware and software support tools. Energy harvesting devices experience power intermittence whichcauses the system to reset and power-cycle unpredictably, tens to hundreds of times per second. This can result incode execution errors that are not possible in continuously-powered systems and cannot be diagnosed with conventionaldebugging tools such as JTAG and/or oscilloscopes. We propose the Energy-interference-free Debugger, ahardware and software platform for monitoring and debugging intermittent systems without adversely effectingtheir energy state. The Energy-interference-free Debugger re-creates a familiar debugging environment for intermittentsoftware and augments it with debugging primitives for effective diagnosis of intermittence bugs. Our evaluationof the Energy-interference-free Debugger quantifies its energy-interference-freedom and shows its value in a set ofdebugging tasks in complex test programs and several real applications, including RFID code and a machine-learning-basedactivity recognition system.